Micro- and nanoplastics current status: legislation, gaps, limitations and socio-economic prospects for future - Osuna-Laveaga, Daryl Rafael; Ojeda-Castillo, Valeria; Flores-Payán, Valentín; Gutiérrez-Becerra, Alberto; Moreno-Medrano, Edgar David (Frontiers in Environmental Science, 2023)
The pollution caused by micro- (MP) and nanoplastics (NP) in the planet's ecosystems has gained significant interest in recent years due to their environmental impact and effects on the health of living organisms. Given this, it is necessary to conduct a comprehensive analysis of the actions required to mitigate their impacts. This paper analyzes existing legislation across different countries and regions, including Europe, North America, China, Russia, India, Brazil, Mexico, and the global initiatives undertaken by the United Nations. Furthermore, it highlights the need for additional measures to mitigate the impact of MP/NP in future years, such as the development of technologies for the separation or degradation of these particles in water intended for human consumption and in wastewater treatment plant effluents, studying plastic particulate material in the air considering meteorological parameters, MP/NP detection protocols in human fluid samples, creating truly biodegradable polymers for use as bioplastics, and establishing institutions responsible for the management of plastic waste. The study also shows the current state of abundance (characterization and quantification) of MP/NP in different environmental matrices based on reports from recent years, and identifies key research opportunities and actions required to evaluate the risks and toxicity associated with MP/NP. Socio-economic aspects are considered, including the impact of MP/NP on different regions, by associating economic and human wellness parameters to plastic waste generation by using available data from 148 countries. As result of this analysis, both the most populated and developed countries contribute to MP/NP generation, however, they have different capacities to address this problem due to social circumstances. The solution to this problem requires efforts from authorities, industry, the scientific community, and the active participation of the population, then, resolving social, political, and economic issues between countries and regions of the world is necessary.